2008
DOI: 10.1088/0954-3899/35/10/104021
|View full text |Cite
|
Sign up to set email alerts
|

The axial anomaly and the phases of dense QCD

Abstract: The QCD axial anomaly, by coupling the chiral condensate and BCS pairing fields of quarks in dense matter, leads to a new critical point in the QCD phase diagram [1, 2], which at sufficiently low temperature may terminate the line of phase transitions between chirally broken hadronic matter and color superconducting quark matter. The critical point indicates that matter at low temperature should cross over smoothly from the hadronic to the quark phase, as suggested earlier on the basis of symmetry. We review h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
225
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(228 citation statements)
references
References 29 publications
3
225
0
Order By: Relevance
“…This is a realization of hadron-quark continuity [10] in the Ginzburg-Landau description. Close similarities to the BEC-BCS crossover in ultra-cold atomic systems are also suggestive [11]. …”
Section: Introductionmentioning
confidence: 67%
“…This is a realization of hadron-quark continuity [10] in the Ginzburg-Landau description. Close similarities to the BEC-BCS crossover in ultra-cold atomic systems are also suggestive [11]. …”
Section: Introductionmentioning
confidence: 67%
“…The arguments presented in [1,2] suggest that we can use the standard kinetic equation in the relaxation-time approximation (RTA) of the form [18][19][20] …”
Section: Relaxation Time Approximationmentioning
confidence: 99%
“…Let us also remember that the pressure of the vacuum for the NJL model was estimated in [9][10][11] to be 40-50 MeV/fm 3 , which is quite consistent with that obtained in the bag model. It was also demonstrated that there is a region of instability within a certain interval of the Fermi momenta generated by the anomalous behavior of pressure d P/dn < 0 (see also [33][34][35][36]). Figure 10 displays fragments of isotherms shown in Fig.…”
Section: Mean Energy As a Functional Of Quantum Liquid Theorymentioning
confidence: 99%
“…If we know the liquid density we obtain the Fermi momentum (P F = 346 MeV) from (35). Applying the identities (37), (38) we have for the particular case b = 0, c = 0 the results C 2 s = 25.3, C 2 v = −0.471, i.e.…”
Section: Transition Layer Between Gas and Liquidmentioning
confidence: 99%